Management of Giant Cell Tumour Radius in a Three Year old Child with an Improvised Technique - Ajay Puri (Journal of Clinical and Diagnostic Research, 2014)
Giant cell tumours of immature skeleton have a very low incidence and epi-metaphyseal location. We are presenting giant cell tumour distal radius in a skeletally immature patient; an uncontained defect with a large soft tissue component which was managed by wide excision and reconstruction with an improvised technique.